Kompleksowe zarządzanie jakością na przykładzie Wojewódzkiego Szpitala Specjalistycznego nr 2 w Bytomiu - Skowron, Krzysztof (Total Quality Management on the Example of Specialist Hospital no. 2 in Bytom, 2006)
This article presents the example of implant the Total Quality Management (TQM) conception in the case of selected hospital in Bytom. Article describes an idea of Total Quality Management and contains a short characteristic and history of this hospital. Than it was described the process of beginning implantation of TQM. Article ends with summary and conclusions from presented case.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 145-152